If x = y2z2 and y= sin(y+ z), then is equal to: a) 2yz? - 2zy2 + 2yz tan(y + z) b) 2yz - y? + y tan(y + z) c) 2yz + y-y tan(y + z) e) 2yz? +2zy-2yz tan(y + z) )z? - 2yz + 2z tan(y + 2) d) z + 2yz - 2z tan(y + z) a b C d e f
If x = y2z2 and y= sin(y+ z), then is equal to: a) 2yz? - 2zy2 + 2yz tan(y + z) b) 2yz - y? + y tan(y + z) c) 2yz + y-y tan(y + z) e) 2yz? +2zy-2yz tan(y + z) )z? - 2yz + 2z tan(y + 2) d) z + 2yz - 2z tan(y + z) a b C d e f
Related questions
Question
![dx
If x = y2z2 and y= sin(y +z), then is equal to:
dy
a) 2yz? - 2zy? + 2yz tan(y + z)
b) Zyz – y? + y tan(y + z)
c) 2yz + y? – y tan(y + z)
d) z? + 2yz – 2z tan(y + z)
e) 2yz? + 2zy? - 2yz tan(y + z)
) z? – 2yz + 2z tan(y + z)
a
b
C
d
e](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2F82897fe2-47fb-4855-95ac-58f37de7c25d%2F040d927a-23fb-4ce4-8a34-5e2487127a59%2Fbimrhvb_processed.jpeg&w=3840&q=75)
Transcribed Image Text:dx
If x = y2z2 and y= sin(y +z), then is equal to:
dy
a) 2yz? - 2zy? + 2yz tan(y + z)
b) Zyz – y? + y tan(y + z)
c) 2yz + y? – y tan(y + z)
d) z? + 2yz – 2z tan(y + z)
e) 2yz? + 2zy? - 2yz tan(y + z)
) z? – 2yz + 2z tan(y + z)
a
b
C
d
e
Expert Solution
![](/static/compass_v2/shared-icons/check-mark.png)
This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
Step by step
Solved in 3 steps
![Blurred answer](/static/compass_v2/solution-images/blurred-answer.jpg)